Developing a Country‐wide Tourist Loyalty Scheme: A Barren Landscape. (28th April 2016) - Zopiatis, Anastasios; Theocharous, Antonis L.; Kosmas, Petros C.; Webster, Craig; Melanthiou, Yioula
Abstract: Loyalty programs, popular in today's competitive business environment, have been capturing the attention of the tourism industry since the mid 80's. While many segments of the industry have successfully utilized loyalty programs, the development of a country‐wide loyalty scheme still poses major challenges. Reflecting the findings of an extensive mixed methods research, the paper set out to empirically investigate tourists' willingness to participate in a country‐wide loyalty scheme, define the incentives they expect from such a scheme, and, explore the perceptions of hospitality stakeholders towards this potential development. Findings are of interest to both academic scholars and industry stakeholders. Copyright © 2016 John Wiley & Sons, Ltd.